Periodontal condition and ultrasound-based measures of arterial stiffness: results of the Health 2000 Survey - Emilia Ollikainen; Tellervo Tervonen; Anna Liisa Suominen; Matti Knuuttila; Antti Jula; Tuomas Saxlin; Pekka Ylöstalo (BMC, 2022)
Abstract Background Periodontitis has been associated with inflammatory processes in arterial walls such as impairment in endothelial function and thickening of intima media. As inflammation plays a role also in arterial stiffening, an association between periodontal inflammation and arterial stiffness can be expected. So far, conflicting results of the association between periodontal disease and arterial stiffness have been reported. Many of the earlier studies were conducted in specific populations and heterogeneous measures of both arterial stiffness and periodontal status were used. In this population-based study we aimed to investigate whether periodontal pocketing and gingival bleeding are associated with ultrasound-based measures of arterial stiffness. Methods In this cross-sectional study, two sets of data based on the national Health 2000 Survey in Finland were formed. Data set I comprised never-smoking 45-64-year-old dentate (≥ 10 natural teeth), non-diabetic, non-rheumatic, non-obese (BMI ≤ 30 kg/m2), non-hypertensive subjects with no coronary artery disease or ongoing lipid-lowering medications (n = 157). Data set II was formed of an unrestricted 45-74-year-old dentate population (n = 536). Four arterial stiffness measures (carotid artery compliance, Peterson's elastic modulus, Young's elastic modulus and beta stiffness index) based on an ultrasound examination of the common carotid artery were used. Periodontal parameters included the number of teeth with ≥ 4 mm deep periodontal pockets and the number of sextants with gingival bleeding. β-estimates, confidence intervals, and p-values were obtained from linear regression models. Results In Data set I, the adjusted β-estimates for the association between the number of teeth with ≥ 4 mm deep periodontal pockets and Peterson's elastic modulus and Young's elastic modulus were 15.80 (p = 0.12) and 61.02 (p = 0.22), respectively. The respective β-estimates were 31.06 (p = 0.17) and 121.16 (p = 0.28) for the association between the number of bleeding sextants and these two stiffness measures. The results in Data set II were in line with the results in Data set I, with the exception that the adjusted β-estimates for the associations between Peterson's elastic modulus and Young's elastic modulus and periodontal parameters were closer to null. Conclusions This population-based study did not provide evidence of an association between periodontal condition and arterial stiffness.